Pelatihan Penulisan Artikel Ilmiah Pada Mahasiswa Semester Akhir - Muhammad Yahrif; R. Supardi (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Training in writing scientific articles is one of the things that is very important for final semester students to know. The publication of scientific articles is one of the requirements that must be met by final semester students before they advance for the final exam. But based on preliminary observations with several final semester students, it turns out that there are still many of them who don't know how to write scientific articles. Some of them even think that writing scientific articles is the same as writing ordinary paper assignments. Based on these findings, it is necessary to hold scientific article writing training for final semester students. This community service used a descriptive method. It is hoped that this scientific article writing training can help final semester students to write and publish their scientific articles, so that they can fulfill one of the pre-requirements for graduating from their studies.